Correlation Between Bioelectrical Impedance Analysis and Chest CT-Measured Erector Spinae Muscle Area: A Cross-Sectional Study - Cao, Jie; Zuo, Didi; Han, Tingting; Liu, Hongxia; Liu, Wenwen; Zhang, Jia; Weng, Yurong; Jin, Xian; Chen, Zengai; Hu, Yaomin (Frontiers in Endocrinology, 2022)
Background: Skeletal muscle mass (SMM) plays an important part in diverse health and disease states. Bioelectrical-impedance analysis (BIA) and computed tomography (CT) are available for its assessment. However, muscle mass assessed by BIA may be influenced by multiple factors. The erector spinae muscle area (ESA) on chest CT is recently presumed to be representative of SMM. This study aimed to derive BIA from the ESA and evaluate the magnitude of association (between ESA measured from chest CT) and BIA. Methods: Subjects hospitalized for health checkups between December 2020 and December 2021, having undergone both BIA (50 kHz, 0.8 mA) and chest CT were included. ESA was quantified at the level of the 12th thoracic vertebra (T12-ESA) by a standardized semi-automated segmentation algorithm. Low SMM was defined, using the Asian Working Group for Sarcopenia criteria. The association between T12-ESA and BIA was then evaluated. Stratified analyses by sex and BMI were also performed Results: Among 606 included subjects (59.7 ± 16.6 years, 63.5% male), 110 (18.2%) had low SMM. BMI in low- and normal- SMM groups was 20.1 and 24.7 kg/m2, respectively. Current smoking, drinking, chronic obstructive pulmonary disease and chronic renal dysfunction were more frequently seen in the low SMM group than in the normal SMM group. The final regression model included T12-ESA, weight, BMI and age, and had an adjusted R2 of 0.806 with BIA. In the validation group, the correlation between T12-ESA-derived BIA and BIA remained high (Pearson correlation = 0.899). Stratified analysis disclosed a stronger correlation between T12-ESA and BIA in males than in females (adjusted R2 = 0.790 vs. adjusted R2 = 0.711, P <0.05), and a better correlation was observed in obese (BMI ≥ 30 kg/m2) compared with underweight (BMI < 18.5 kg/m2) (adjusted R2 =0.852 vs. adjusted R2 = 0.723, P <0.05). Additional analysis revealed a significant correlation between T12-ESA and skeletal muscle cross-sectional area at the 3rd lumbar vertebra (L3-CSA) (adjusted R2 = 0.935, P <0.001). Conclusions: CT-based assessment of ESA at T12 level is feasible and correlated well with BIA, especially in males and obese subjects.